Accelerometer-Based Physical Activity Patterns and Associations With Outcomes Among Individuals With Osteoarthritis. Issue 2 (26th March 2022) - Beauchamp, Tyler; Arbeeva, Liubov; Cleveland, Rebecca J.; Golightly, Yvonne M.; Hales, Derek P.; Hu, David G.; Allen, Kelli D.
Abstract : Background: This study examined patterns of physical activity and associations with pain, function, fatigue, and sleep disturbance among individuals with knee or hip osteoarthritis. Methods: Participants (n = 54) were enrolled in a telephone-based physical activity coaching intervention trial; all data were collected at baseline. Self-reported measures of pain and function (WOMAC [Western Ontario and McMaster Universities Osteoarthritis Index] subscales), fatigue (10-point numeric rating scale), and PROMIS (Patient-Reported Outcomes Information System) Sleep Disturbance were collected via telephone. Accelerometers were mailed to participants and were worn for at least 3 days. Proportion of time participants spent in sedentary behavior during the morning (from wake until 12:00 pm ), afternoon (12:00 pm until 5:59 pm ) and evening (6:00 pm until sleep) each day was averaged across all days of wear. Pearson correlations assessed associations between activity and self-reported measures. Results: Participants spent a large proportion of time in sedentary behavior: 65.6% of mornings, 70.0% of afternoons, and 76.6% of evenings. Associations between proportion of time spent in sedentary behavior and reported outcomes were generally strongest in the afternoon, strongest for WOMAC function, and lowest for PROMIS Sleep Disturbance. In the evening hours, sedentary time was most strongly associated with fatigue. Conclusions: Overall, findings stress the importance of reducing sedentary behavior among adults with osteoarthritis and suggest behavioral interventions may be strengthened by considering patients' within-day variation in symptoms and activity.